Performance Studies of the Domestic Effluent Treatment Plant at ITI Bangalore - KUMAR THAPA, SRIDHAR GAUTAM, UMESH B, RAJASEKAR G and SUNIL KUMAR G (1992)
INTERNAL GUIDE: B S SHANKAR, MVJCE
Keywords: Domestic Effluent Treatment Plant